IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM PRAKTIK PENDIDIKAN - Atin Supriatin; Aida Rahmi Nasution (Jurusan PGMI FTIK IAIN Metro Lampung, 2017)
Indonesia is a multicultural country consisting of different tribes, languages ​​and religions. This diversity, on one hand, is one of the advantages and wealth of the nation that must be maintained. But on the other hand, this diversity can be a potential conflict in the midst of society. Therefore, the understanding of the motto of